Manifestation of dynamic Jahn-Teller distortions and surface interactions in scanning tunnelling microscopy images of fullerene anion C−60 - Dunn, Janette L.; Lakin, Andrew J.; Hands, Ian D. (IOP Publishing, 2012)
Using scanning tunnelling microscopy (STM), it is possible to observe detailed structure of the molecular orbitals (MOs) of fullerene anions C−60. However, understanding the experimental observations is not straightforward because of the inherent presence of Jahn–Teller (JT) interactions, which (in general) split the MOs in one of a number of equivalent ways. Tunnelling between equivalent distortions means that any observed STM image will be a superposition of images arising from the individual configurations. Interactions with the surface substrate must also be taken into account. We will show how simple ideas involving a symmetry analysis and Hückel molecular orbital theory can be used to understand observed STM images without need for the more usual but more complicated density functional calculations. In particular, we will show that when the fullerene ion is adsorbed with a pentagon, hexagon or double-bond facing the surface, STM images involving the lowest unoccupied molecular orbital (LUMO) can be reproduced by adding together just two images of squares of components of the LUMO, in ratios that depend on the strength of the JT effect and the surface interaction. It should always be possible to find qualitative matches to observed images involving any of these orientations by simply looking at images of the components, without doing any detailed calculations. A comparison with published images indicates that the JT effect in the C−60 ion favours D3d distortions.